Transcriptome of melanoma cells from two mouse models, Tyr:NRas(Q61K)and Tyr:Rack1-HA, Tyr:NRas(Q61K) - Campagne, Cécil (Data Brief, 2017)
The transcriptome sequencing of melanoma cells from two mouse models differing in the expression level of the scaffold protein Receptor for activated C kinase (RACK1) are presented. Primary melanoma cells were harvested from Tyr:NRas(Q61K); Pax3(GFP/+) mice, with or without the Tyr:Rack1-HA transgene. Cells were cultured and infected with scramble shRNA or Rack1-targeting shRNA, on technical triplicates of viral infection. Libraries were prepared by selecting polyadenylated mRNAs and RNA Sequencing (RNASeq) was performed. Samples are described in the SRA portal (SRP096162) and FASTQ files have been deposited in Sequence Read Archive (accession numbers: SRR5150106 to SRR5150117). The interpretation of these data is presented in the following research article: “RACK1 cooperates with NRAS(Q61K) to promote melanoma in vivo” (Campagne et al., 2017, doi: 10.1016/j.cellsig.2017.03.015) [1].